Estimating the Effects of Aggregate Agricultural Growth on the Distribution of Expenditures - Ligon, Ethan; Sadoulet, Elisabeth (Washington, DC: World Bank, 2012)
Different approaches toward estimating the effects of agricultural growth on expenditure growth and distribution are explored. The question is how do changes in the sectoral composition of income affect the distribution of expenditures across households within a country. The study finds that agricultural income growth has a particularly beneficial effect for the poorest households (in terms of expenditures), while the benefits of non-agricultural income growth are much more modest. Conversely, the benefits of agricultural income growth dissipate for higher expenditure households, while the benefits of non-agricultural income growth are increasing. The evidence presented here is generally consistent with the view that agricultural income growth is more effective at reducing poverty than is growth in other sectors